PELANGGARAN HAK ASASI MANUSIA MASYARAKAT MINORITAS JEMAAT AHMADIYAH (Studi Kasus : Perusakan Masjid Al-Kautsar Jemaat Ahmadiyah di Desa Purworejo Kecamatan Ringinarum Kabupaten Kendal Tahun 2016) - Diah Wijayana; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2019)
Cases of social violence is amount on behalf of religion carried out by intolerant groups against to Jemaat Ahmadiyah made the writer interested in carrying out this research. Destruction Mosque’s Al-Kautsar of Jemaat Ahmadiyah in Kendal, aren’t the first time an action violations community of human rights by intolerant group in Indonesia. This research to determine how the beginning of the presence Jemaat Ahmadiyah, to describe the causes of the destruction of the Al-Kautsar’s Mosque by Jemaat Ahmadiyah, and to identify the factors that caused the destruction of the Al-Kautsar’s Mosque by Jemaat Ahmadiyah Purworejo, Ringinarum, Kendal. The method of research is descriptive qualitative with techniques data collection with interviews, observation, and document review. The data obtained is then analyzed using data source triangulation.The results of the research is the beginning of the first time Jemaat Ahmadiyah in Purworejo, the presence of Jemaat Ahmadiyah in Purworejo wasn’t fully acceptable to the people of Purworejo Village. As a minority community in this village, Jemaat Ahmadiyah often gets discrimination from intolerant people in their villages. The determination of the Fatwa’s MUI and the SKB Tiga Menteri is always the reason for intolerant groups to carry out intolerant actions. The feeling hatred from society to Jemaat Ahmadiyah made the people have to destroy Al-Kautsar’s Mosque of the Jemaat Ahmadiyah. The factors underlying the destruction of the mosque are due to minority factors, social factors, religious factors and policy factors. The need for an attention government stance in establishing law and describing a small amount of space for minority society can minimize the occurrence of acts of discrimination among majority society with minority society.Key Words : Ahmadiyah, Destruction, Mosque, Government, Minority